PENGARUH PROGRAM BANK SAMPAH TERHADAP TINGKAT PENDAPATAN KELUARGA NASABAH BANK SAMPAH MANDIRI DI KELURAHAN KEBONSARI - Ani Umyati; Yanyan Dwiyanti; Tri Partuti (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2018)
This research is a qualitative and quantitative research that aims to find out and analyze the influence of waste bank program on the income of customers Mandiri Garbage Bank in Kebonsari Village, Citangkil District, Cilegon City. The population were 50 customers of Mandiri Garbage Bank, consisting of administrators (9 people), active members (15 people) and non-active members (26 people). Data collection methods used are questionnaires, observation, documentation and interviews. Data was analysed with linearregression formula. It’s obtained the value of the bank's waste program (X) in 1 unit, it will cause a decreasein the value of the customer's family income (Y) which is 0.287 per unit. Hypothesis approvened by using the t test, and the result is no influence of the waste bank program variables on the variable income level of the customer family of Mandiri Garbage Bank in Kebonsari Village, Citangkil District, Cilegon City. This is evident from the value of t count (-1,981) <t table (2,012).